MiR-21 Regulating Distribution of Intestinal Flora Through TNF-α Promotes Progression of Ulcerative Colitis: MiR-21 Promotes Development of Ulcerative Colitis - Yang, Ke; Liu, Xueni; Niu, Tao; Zhao, Qiang; Gao, Feng (Journal of Medical Biochemistry, 2023)
Background: To study the changes in intestinal flora in patients with ulcerative colitis (UC), and to explore its correlations with micro ribonucleic acid (miR)-21 and serum tumor necrosis factor-α (TNF-α).Methods: A total of 150 patients with UC were selected and divided into remission group and seizure group according to the severity of disease. At the same time, 150 healthy people receiving physical examination in the hospital during the same period were selected as control group. The levels of fecal miR-21 and TNF-α in all subjects were determined via reverse transcription-polymerase chain reaction (RT-PCR). The correlation between miR-21 and TNF-α and their associations with the changes in intestinal bacteria in UC were analyzed using Pearson correlation analysis. The risk factors affecting the occurrence of UC were explored via multivariate logistic regression analysis. Results: The levels of fecal miR-21 and TNF-α in patients with UC were significantly higher than those in control group, and they were also significantly higher in seizure group than those in remission group. There was a positive correlation between the levels of miR-21 and TNF-α. The number of fecal intestinal flora (Bifidobacterium, Lactobacillus, Enterobacterium and Enterococcus) was different in patients with varying degrees of disease. MiR-21 and TNF-α were negatively correlated with the content of Bifidobacterium and Lactobacillus, but positively correlated with the content of Enterobacterium and Enterococcus. According to multivariate logistic regression analysis, miR-21 and TNF-α were risk factors for the seizure of UC.Conclusion: MiR-21 can promote the expression of TNF-α, and lead to the alteration of intestinal flora, thereby enhancing the occurrence and development of UC.
Keywords: Ulcerative colitis; intestinal flora; miR-21; TNF-α